Optimal Magnetic Resonance Sequence for Assessment of Central Cartilage Tumor Scalloping - Shirodkar, Kapil K.; Jenko, Nathan; Azzopardi, Christine; Murphy, Jennifer; Patel, Anish; James, Steven L.; Davies, Arthur Mark; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2024)
Background Magnetic resonance imaging (MRI) is key in evaluating central cartilage tumors. The BACTIP (Birmingham Atypical Cartilaginous Tumour Imaging Protocol) protocol assesses central cartilage tumor risk based on the tumor size and degree of endosteal scalloping on MRI. It provides a management protocol for assessment, follow-up, or referral of central cartilage tumors.Objectives Our study compared four MRI sequences: T1-weighted (T1-w), fluid sensitive (Short Tau Inversion Recovery (STIR)- weighted, STIR-w), and grayscale inversions (T1-w GSI and short tau inversion recovery [STIR] GSI) to see how reliably endosteal scalloping was detected.Materials and Methods Two senior consultant musculoskeletal radiologists with experience reviewed randomly selected 60 representative central cartilage tumor cases with varying degree of endosteal scalloping to reflect a spectrum of BACTIP pathologies. The endosteal scalloping was graded as per the definition of BACTIP A, B, and C. They agreed on a consensus BACTIP grade for each of the 240 key images (60 cases × 4 sequences), which was considered the final “consensus” BACTIP grade. These 240 images were then randomized into a test set and given to two fellowship-trained consultant musculoskeletal radiologists for analysis. They assigned a BACTIP grade to each of the 240 selected images while being blinded to the final “consensus” BACTIP grade. The training set was further subdivided into three groups based on the MR image quality (good quality, average quality, and poor quality) to ascertain if the quality of the acquired images influenced intraobserver and interobserver agreements on the BACTIP grading. The two observers were blinded to the grade assigned to the image quality.Results Linearly weighted kappa analysis was performed to measure the agreement between the BACTIP grading answers by two observers and the “consensus” BACTIP grading answers, as well as the BACTIP grading agreement between the two observers themselves. The analysis revealed that T1-w and STIR-w sequences demonstrated more consistent and higher agreement across different image qualities. However, the T1-w GSI and STIR-w GSI sequences exhibited lower agreement, particularly for poor-quality images. T1-w imaging demonstrated substantial agreement between BACTIP gradings for poor-quality images, suggesting potential resilience of T1-w sequence in challenging imaging conditions.Conclusion T1-w imaging is the best sequence for BACTIP grading of endosteal scalloping, followed by fluid-sensitive STIR sequences.
Keywords: BACTIP; endosteal scalloping; MRI; GSI; central cartilage tumor; chondrosarcoma